Pengaruh Komunikasi Kepala Madrasah Terhadap Peningkatan Keterlibatan Masyarakat di Madrasah Aliyah Nurus Sholah Akkor Pamekasan - Mohammad Kosim; Jamaluddin Akbar (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2018)
Schools and communities (publics) are two entities that can not be separated in supporting the implementation of education in an educational institution. In this case, the principal (Head of Madrasah) has an important role in establishing and maintaining relationships between the school and community elements around the school. One of the most important aspects of good duties and leadership of Madrasah principals is the communication aspect. The communication in question is how the head of Madrasah builds synergy between the school community (school environment) and builds good relations with the environment around the school or the communities around the school. This research is a quantitative descriptive research that aims to find out how far the influence of madrasah principal communications to increase community involvement in MA Nurus Sholah by using the product moment correlation formula that its descriptions are calculated based on the numbers obtained from the questionnaire results. The results of the study indicate that Madrasah head communication influenced the increasing of community involvement in Madrasah Aliyah Nurus Sholah Akkor Pamekasan. This is evidenced by the value of